Outcomes of transfemoral-transcatheter aortic valve replacement with Sapien-3 valve in liver cirrhosis patients. (14th October 2021) - Lak, H; Chawla, S; Verma, B; Vural, A; Gad, M; Shekhar, S; Nair, R; Yun, J; Burns, D; Puri, R; Reed, G; Harb, S; et al.
Abstract: Background: Little is known about the outcomes of liver cirrhosis patients with severe aortic stenosis (AS) who undergo transcatheter aortic valve replacement (TAVR). Methods: We undertook a retrospective analysis of consecutive patients with severe symptomatic AS who underwent transfemoral-TAVR with Sapien-3 valve at our Clinic between April 2015 and December 2018, yielding 32 patients with liver cirrhosis on imaging including ultrasound and/or computed tomography. Their baseline characteristics, procedural and long-term outcomes after TAVR with the non-cirrhotic group were compared, along with their management strategies as per the hepatology team. Results: Among 1028 patients, 32 were assigned to the cirrhosis, and 996 were assigned to the non-cirrhosis (control) group. Compared with the control group cirrhotic patients were slightly younger in age (74.5 vs 81.2 years), had a slightly higher BMI (31.3 vs 29.3), and had a higher incidence of prior history of myocardial infarction (38% vs 33%). Baseline variables including the history of smoking, hypertension, diabetes, and atrial fibrillation were comparable in both groups. Among cirrhotic patients (n=32), the most common etiologies were non-alcoholic steatohepatitis (NASH) (37.5%), Alcoholism (18.75%), and Hepatitis C (12.5%). The mean MELD-NA score was 11.8 and 67% of patients were Child PUGH Class A and 33% were Child PUGH Class B and all patients had a Child PUGH score of ≥5. 53% of patients (n=17) in the cirrhosis group were evaluated by Hepatology and 12.5% (n=4) were evaluated for a liver transplant but only 1 patient had a liver transplant post-TAVR. Compared with the control group cirrhotic patients had similar 1-year mortality (12% vs 12%, p=1), had a lower rate of 30-day new pacemaker post tavr (6% vs 9% p=0.85), had a higher rate of 1-year readmission for heart failure (12% vs 5% p=0.12) and similar 1-year major adverse cardiac and cerebrovascular event (MACCE) rate (15% vs 14% p=0.98) Conclusion: Patients with severe AS undergoing TAVR with concomitant liver cirrhosis demonstrate comparable outcomes compared with their non- cirrhotic counterparts. NASH followed by alcoholic cirrhosis was found to be most common etiology. Funding Acknowledgement: Type of funding sources: None.